Answer:
Step-by-step explanation:
Multiplying x+6y=-3 with 2 so its equal to first eqn,
Eliminating,
2x + 3y = 3 (1)
2x +12y = -6 (2) (because subtracting)
------------------
-9y =9
∴y=-1
eq. y in 1
2x -3=3
2x=3+3
x=6/2
=3
Pls mark me brainliest
For this case you must simplify the expression respecting the rules of multiplication of mathematics.
The steps to simplify the expression are the following:
First multiply what is in the parentheses
-2x ^ 2 (x - 5) + x (2x ^ 2 - 10x) + x
-2x ^ 3 + 10x ^ 2 + 2x ^ 3 - 10x ^ 2 + x
Then add the terms that have the same exponent
(-2x ^ 3 + 2x ^ 3) + (10x ^ 2 - 10x ^ 2) + x
x
The final simplification is
x
answer
x
Answer:
Estimate = 0.4
Quotient = 0.355 ---> Approximated to nearest thousandth
Step-by-step explanation:
Question like this is better answered using attachment;
See Attachment
When 1.066 is divided by 3,
The quotient is 0.3553......
When estimating to tenths,
We stop the quotient at 0.35 then round it up.
This gives 0.4
When estimating to nearest thousandth,
We stop the quotient at 0.3553 then round it up;
This gives 0.355
<h3>#End behaviour:-</h3>
#1
#2
<h3>#Degree:-</h3>
Find nodes
#1
#2
It's a parabola so it's the graph of a quadratic equation.
<h3>Real zeros</h3>
#1
#2
Given problem is ![\frac{(5+2i)}{(6+i)}](https://tex.z-dn.net/?f=%5Cfrac%7B%285%2B2i%29%7D%7B%286%2Bi%29%7D)
To simplify that we need to multiply and divide by conjugate of the denominator
conjugate of denominator 6+i will be 6-i as we just need to change sign of the imaginary part
Now multiply and divide by 6-i
![=\frac{(5+2i)}{(6+i)}\cdot\frac{(6-i)}{(6-i)}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B%285%2B2i%29%7D%7B%286%2Bi%29%7D%5Ccdot%5Cfrac%7B%286-i%29%7D%7B%286-i%29%7D)
![=\frac{30-5i+12i-2i^2}{36-6i+6i-i^2}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B30-5i%2B12i-2i%5E2%7D%7B36-6i%2B6i-i%5E2%7D)
![=\frac{30+7i-2i^2}{36-i^2}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B30%2B7i-2i%5E2%7D%7B36-i%5E2%7D)
![=\frac{30+7i-2\left(-1\right)}{36-\left(-1\right)}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B30%2B7i-2%5Cleft%28-1%5Cright%29%7D%7B36-%5Cleft%28-1%5Cright%29%7D)
![=\frac{30+7i+2}{36+1}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B30%2B7i%2B2%7D%7B36%2B1%7D)
![=\frac{32+7i}{37}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B32%2B7i%7D%7B37%7D)
![=\frac{32}{37}+\frac{7}{37}i](https://tex.z-dn.net/?f=%3D%5Cfrac%7B32%7D%7B37%7D%2B%5Cfrac%7B7%7D%7B37%7Di)
Hence final answer is ![\frac{32}{37}+\frac{7}{37}i](https://tex.z-dn.net/?f=%5Cfrac%7B32%7D%7B37%7D%2B%5Cfrac%7B7%7D%7B37%7Di)